Drosophila myt1 is the major cdk1 inhibitory kinase for wing imaginal disc development. - Jin, Z.; Homola, E.; Tiong, S.; Campbell, S.D. (Genetics, 2008)
Mitosis is triggered by activation of Cdk1, a cyclin-dependent kinase. Conserved checkpoint mechanisms normally inhibit Cdk1 by inhibitory phosphorylation during interphase, ensuring that DNA replication and repair is completed before cells begin mitosis. In metazoans, this regulatory mechanism is also used to coordinate cell division with critical developmental processes, such as cell invagination. Two types of Cdk1 inhibitory kinases have been found in metazoans. They differ in subcellular localization and Cdk1 target-site specificity: one (Wee1) being nuclear and the other (Myt1), membrane-associated and cytoplasmic. Drosophila has one representative of each: dMyt1 and dWee1. Although dWee1 and dMyt1 are not essential for zygotic viability, loss of both resulted in synthetic lethality, indicating that they are partially functionally redundant. Bristle defects in myt1 mutant adult flies prompted a phenotypic analysis that revealed cell-cycle defects, ectopic apoptosis, and abnormal responses to ionizing radiation in the myt1 mutant imaginal wing discs that give rise to these mechanosensory organs. Cdk1 inhibitory phosphorylation was also aberrant in these myt1 mutant imaginal wing discs, indicating that dMyt1 serves Cdk1 regulatory functions that are important both for normal cell-cycle progression and for coordinating mitosis with critical developmental processes.